Performance of Clinical Nurse Educators in Teaching Pharmacology and Medication Management: Nursing Students’ Perceptions - Ghamari Zare; Adib-Hajbaghery (Nursing and Midwifery Studies, 2016)

(untitled)
Background Pharmacological knowledge and medication management skills of student nurses greatly depend on the clinical nurse educators’ performance in this critical issue. However, the Iranian nurse educators’ performance in teaching pharmacology and medication management are not adequately studied.